2012
DOI: 10.1016/j.smrv.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms, sleep, and substance abuse

Abstract: Substance abuse is linked to numerous mental and physical health problems, including disturbed sleep. The association between substance use and sleep appears to be bidirectional, in that substance use may directly cause sleep disturbances, and difficulty sleeping may be a risk factor for relapse to substance use. Growing evidence similarly links substance use to disturbances in circadian rhythms, although many gaps in knowledge persist, particularly regarding whether circadian disturbance leads to substance ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
157
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(176 citation statements)
references
References 93 publications
5
157
1
6
Order By: Relevance
“…Similar to mental health, a bi-directional relationship has been demonstrated between substance use and sleep. In other words, using substances with sedating and soporific effects can affect circadian rhythms and directly cause sleep disturbances; conversely, sleep difficulties appear to increase the risk of substance misuse (Hasler et al, 2012;Wong, Robertson, & Dyson 2015). Metha et al (2014) concluded from their study of college students in the U.S., that there was an association between friendship and substance use.…”
Section: Contributing Factors To Sleep Deficiency and Help Seeking Bementioning
confidence: 99%
“…Similar to mental health, a bi-directional relationship has been demonstrated between substance use and sleep. In other words, using substances with sedating and soporific effects can affect circadian rhythms and directly cause sleep disturbances; conversely, sleep difficulties appear to increase the risk of substance misuse (Hasler et al, 2012;Wong, Robertson, & Dyson 2015). Metha et al (2014) concluded from their study of college students in the U.S., that there was an association between friendship and substance use.…”
Section: Contributing Factors To Sleep Deficiency and Help Seeking Bementioning
confidence: 99%
“…That is, sleep problems predict problem behaviours, while problem behaviours increase sleep problems as well (e.g., Hasler et al 2012). In the current study, this reciprocal relationship between sleep problems and other problem behaviours is tested in young adolescents.…”
Section: The Current Studymentioning
confidence: 99%
“…De hecho, las personas con problemas de abuso y/o dependencia de sustancias suelen presentar un aplanamiento de la amplitud de las funciones circadianas y un retraso horario de los valores máximos, pudiéndose producir incluso un estado de desincronización del control endógeno (Adan, 2010;Conroy et al, 2012;Hasler, Smith, Cousins y Bootzin, 2012). Esta alteración de la ritmicidad circadiana deriva en dificultades de adaptación a los cambios ambientales y se asociaría con un amplio rango de alteraciones.…”
Section: Consumo Abuso Y Dependencia De Sustanciasunclassified